INTELLIGENCE AND HERDSMEN THREATS TO NIGERIA NATIONAL SECURITY: A STUDY OF BENUE STATE - Udeh, Shedrack Chijioke; Maduka, Anthony Chikaodi; Unegbu, George Nze (African Journal of Social and Behavioural Sciences, 2021)
In the past few years especially between 2015 and 2018, the orgy of violence and indiscriminate slaughter of human beings by Fulani herdsmen in Benue State has underscored the imperative of intelligence as a central element in nipping the acts of violent extremism in the bud, hence leveraging national security in Nigeria. The indices of intelligence include gathering, interpreting analyzing, sharing, storing, utilization and feedback. This study examined factors responsible for the herdsmen and farmers clashes. Besides, it identified the challenges of intelligence as a central element in checking herdsmen threats and suggested measures needed to combat herdsmen and farmers clashes. The study adopted secondary method of data collection as its main sources of data. The secondary method of data collection included textbooks, magazines, newspapers, articles, journals, colloquium, etc. However, the study adopted library research and documentary evidence as its method of data analysis. The study adopted Frustration Aggression theory as its theoretical framework. The study shows that the reason for the seeming failure to control the herdsmen threats can be attributed to inadequate or failure of intelligence gathering and sharing mechanism among the security agencies both within and outside the country. The study recommends improved intelligence gathering and sharing mechanism among the security agencies both within the country, and between Nigeria and her neighbours.